2020
DOI: 10.1186/s12970-020-00376-3
|View full text |Cite
|
Sign up to set email alerts
|

Supplement with whey protein hydrolysate in contrast to carbohydrate supports mitochondrial adaptations in trained runners

Abstract: Background Protein supplementation has been suggested to augment endurance training adaptations by increasing mixed muscle and myofibrillar protein synthesis and lean body mass. However, a potential beneficial effect on mitochondrial adaptations is yet to be clarified. The aim of the present study was to investigate the effect of consuming whey protein hydrolysate before and whey protein hydrolysate plus carbohydrate (PRO-CHO) after each exercise session during a six-week training period compared to similarly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(88 reference statements)
0
2
1
Order By: Relevance
“…Thus, we cannot out rule the possibility that the present study's pre-post protein supplementation protocol (2 × 10 g protein doses supplying 0.2 g/kg body weight) and a lower weekly training frequency was insufficient to further enhance these cardiovascular adaptations compared to the Carbohydrate control group. In contrast to both our and Ferguson-Stegall et al's studies, Hansen et al ( 16 ) showed in a 6-week intervention that pre-post exercise ingestion of 0.3 g protein/kg body weight (~40 g protein) significantly increased Cytochrome C protein content compared to isocaloric intake of carbohydrates in trained runners but with no difference in . Several other mitochondrial proteins including SDHA, COX-IV, VDAC and HSP60 followed a similar, although non-significant, pattern.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Thus, we cannot out rule the possibility that the present study's pre-post protein supplementation protocol (2 × 10 g protein doses supplying 0.2 g/kg body weight) and a lower weekly training frequency was insufficient to further enhance these cardiovascular adaptations compared to the Carbohydrate control group. In contrast to both our and Ferguson-Stegall et al's studies, Hansen et al ( 16 ) showed in a 6-week intervention that pre-post exercise ingestion of 0.3 g protein/kg body weight (~40 g protein) significantly increased Cytochrome C protein content compared to isocaloric intake of carbohydrates in trained runners but with no difference in . Several other mitochondrial proteins including SDHA, COX-IV, VDAC and HSP60 followed a similar, although non-significant, pattern.…”
Section: Discussioncontrasting
confidence: 96%
“…Several other mitochondrial proteins including SDHA, COX-IV, VDAC and HSP60 followed a similar, although non-significant, pattern. However, the primary aim of the study by Hansen et al ( 16 ) was to detect differences in mitochondrial adaptations and was not powered to detect differences in performance outcomes, and it is difficult to translate these results to populations with lower training status such as our cohort. Other studies on endurance training have shown that adding protein to carbohydrate drinks in connection to training suppressed markers of muscle damage 12–24 h post-exercise or improved both performance and recovery ( 42 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the level of protein syntheses, another key part of the molecular regulation of cellular phenotype, most acute studies show evidence for substantially increased skeletal-muscle myofibrillar protein synthesis from whey protein (or whey and leucine) ingestion associated with exercise (Breen et al 2011;Churchward-Venne et al 2019;Coffey et al 2011;Rowlands et al 2015), but effects on mitochondrial fraction are largely neutral (Breen et al 2011;Churchward-Venne et al 2019;Coffey et al 2011). There is some evidence, albeit mixed, however, to suggest that chronic whey protein added to a carbohydrate consumed during and after endurance exercise may accentuate mitochondrial adaptation; for example, vs isocaloric non-protein controls, 2 week supplementation in trained men increased skeletal muscle peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1a) (Hill et al 2013), 6 weeks of a milk protein supplement increased maximal oxygen uptake (V _ O 2max ), but without change on accumulated muscle protein in aged men (Robinson et al 2011), and 6-weeks of protein plus carbohydrate supplementation produced significant increases in some but not all mitochondrial proteins measured (Hansen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It's recommended that athletes consume 30-60 g of carbohydrate drinks every 15-20 minutes during exercise (Naclerio et al, 2019;Olsen et al, 2010;Liang et al, 2022). This regimen helps to maintain optimal energy levels and offset mineral loss Proteins for Energy and Recovery, While carbohydrates take the lead in energy provision, proteins play a role as intermediaries in energy production pathways (Hansen et al,2020;Goldstein et al,2022).…”
Section: Resultsmentioning
confidence: 99%